DETERMINATION OF MAXIMUN RETENTION OF BIOACTIVE COMPOUNDS AND ANTIOXIDANT CAPACITY ON NECTAR OF TREE TOMATO (Solanum betaceaum Cav.) - Rojas Benites, Daniella S. (2017)
The appropriate parameters to produce nectar of tree tomato (Solanum betaceaum Cav.), with a greater retention on the content of ascorbic acid, phenolic compounds, total carotenoids and antioxidant capacity that are present in the raw material, were established. The content of bioactive compounds in the tree tomato pulp was determined: total carotenoids with 4,27 mg β-carotene/100g, vitamin C with 28,83 mg ascorbic acid/ 100g, phenolic compounds with 100,55 mg AGE/100g and the antioxidant capacity with 3,3172 μmol trolox/g measured by the DPPH method and 4,6551 μmol trolox/g measured by the ABTS method. A greater retention on the bioactive compounds and antioxidant capacity on the tree tomato nectar was obtained at a pH of 3,33, °Brix of 13, dilution water:pulp of 1:2,5 and a pasteurization temperature of 99,5°C for 1 minute, finding on it a content of 1,68 mg β-carotene/100g, vitamin C of 11,45 mg de ascorbic acid/100g, phenolic compounds of de 32,96 mgAGE/100g y the antioxidant capacity of de 1,3803 μmol trolox/g measured by the DPPH method and 2,0006 μmol trolox/g measured by the ABTS method.